A multicomponent γ-type (Gd1/6Tb1/6Dy1/6Tm1/6Yb1/6Lu1/6)2Si2O7 disilicate with outstanding thermal stability. Issue 11 (1st November 2020) - Sun, Luchao; Luo, Yixiu; Ren, Xiaomin; Gao, Zenghua; Du, Tiefeng; Wu, Zhen; Wang, Jingyang
ABSTRACT: A multicomponent rare-earth disilicate (Gd1/6 Tb1/6 Dy1/6 Tm1/6 Yb1/6 Lu1/6 )2 Si2 O7 has been designed and successfully synthesized following the strategy of high entropy engineering. The as-prepared single-phase 6RE-disilicate possesses a new γ-type crystal structure (monoclinic, P 21 / c ) beyond the α-, β- and δ-type parent structures of six single RE disilicates. Six-species RE cations are homogeneously distributed on RE lattice sites and our multicomponent disilicate demonstrates outstanding thermal stability from room temperature up to around 1900°C. This work extends the knowledge of strategic multicomponent modification of complex ceramics with extremely high phase stability. IMPACT STATEMENT: The first multicomponent γ-type RE2 Si2 O7, (Gd1/6 Tb1/6 Dy1/6 Tm1/6 Yb1/6 Lu1/6 )2 Si2 O7 with outstanding phase stability is developed. It presents the possibility to design complex oxide through the 'one-from-none' strategy. GRAPHICAL ABSTRACT: UF0001